Hyperphosphatemic Tumoral Calcinosis With Pemigatinib Use - Akshan Puar, MBBS; Diane Donegan, MD; Paul Helft, MD; Matthew Kuhar, MD; Jonathan Webster, MD; Megana Rao, BS; Michael Econs, MD (AACE Clinical Case Reports, 2022)
Background/Objective: Pemigatinib, a fibroblast growth factor receptor (FGFR) 1-3 inhibitor, is a novel therapeutic approach for treating cholangiocarcinoma when an FGFR fusion or gene rearrangement is identified. Although the most reported side effect of pemigatinib is hyperphosphatemia, tumoral calcinosis with soft tissue calcifications is not widely recognized as a complication. We report a case of patient with hyperphosphatemic tumoral calcinosis on pemigatinib. Case Report: A 59-year-old woman with progressive metastatic cholangiocarcinoma, despite receiving treatment with cisplatin and gemcitabine for 7 months, was found to have an FGFR2-BICC1 fusion in the tumor on next-generation sequencing. Pemigatinib was, therefore, initiated. Four months into the therapy, multiple subcutaneous nodules developed over the lower portion of her back, hips, and legs. Punch biopsies revealed deep dermal and subcutaneous calcifications. Investigations revealed elevated serum phosphorus (7.5 mg/dL), normal serum calcium (8.7 mg/dL), and elevated intact fibroblast growth factor-23 (FGF23, 1216 pg/mL; normal value <59 pg/mL) levels. Serum phosphorus levels improved with a low-phosphorus diet and sevelamer. Calcifications regressed with pemigatinib discontinuation. Discussion: Inhibition or deficiency of FGF-23 results in hyperphosphatemia and can lead to ectopic calcification. Pemigatinib, a potent inhibitor of FGFR-1-3, blocks the effect of FGF-23 leading to hyperphosphatemia and tumoral calcinosis as observed in our case. Treatment is aimed primarily at lowering serum phosphate levels through dietary restriction or phosphate binders; however, the regression of tumoral calcinosis can occur with pemigatinib cessation, as seen in this case. Conclusion: As the use of FGFR 1-3 inhibitors becomes more prevalent, we aim to raise attention to the potential side effects of tumoral calcinosis.